2017
DOI: 10.1017/s0266462317000411
|View full text |Cite
|
Sign up to set email alerts
|

Do Study Results Translate Into Practice? Intracranial Stenting in Germany

Abstract: Our analysis of German claims data provides little evidence of changed indications for stenting in cases of intracranial atherosclerotic disease which one might expect to be caused by the emergence of high-level evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results of the SAMMPRIS trial and the Vitesse Intracranial Stent Study for Ischemic Stroke Therapy (VISSIT) trial supported the use of medical management alone as being superior to stenting plus medical management [ 15 , 16 ]. There were few indications changed for stenting in cases of intracranial atherosclerosis stenosis [ 17 ]. However, studies from other authors indicated promising outcomes for stent therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the SAMMPRIS trial and the Vitesse Intracranial Stent Study for Ischemic Stroke Therapy (VISSIT) trial supported the use of medical management alone as being superior to stenting plus medical management [ 15 , 16 ]. There were few indications changed for stenting in cases of intracranial atherosclerosis stenosis [ 17 ]. However, studies from other authors indicated promising outcomes for stent therapy.…”
Section: Introductionmentioning
confidence: 99%